Childcare task division and shared parenting attitudes in dual-earner families with young children. - Ehrenberg, Marion F.; Gearing-Small, Margaret; Hunter, Michael A. (Family Relations, 2001)
A study was conducted to determine the attitudes of dual-earner couples to shared parenting (SP), marital satisfaction, and division of child-care tasks. Findings revealed that psychological and relational SP dimensions predicted marital fulfillment, parental competence, and closeness to children; but division of child-care tasks did not. These results were interpreted as indicating how family practitioners can educate and help dual-earner couples with regard to these relational aspects of shared parenting.